High body weight-related retinal vasculopathy in children with obesity. Issue 2 (March 2022) - Dereli Can, Gamze; Kara, Özlem; Can, Mehmet Erol
Purpose: To investigate the foveal avascular zone (FAZ) and the microvascular alterations in both macula and peripapillary region in obese children. Methods: We included a total of 222 eyes of 111 children (54 obese children and 57 healthy subjects). Capillary vessel density (VD) of superficial (SCP) and deep (DCP) retinal capillary plexuses were measured in macular slabs. Peripapillary region was also evaluated. The FAZ parameters were measured based on the whole retinal slab. A commercial optical coherence tomography-angiography system was used. Results: The mean ages were 13.33 ± 2.55 years (range, 8–17) and 13.41 ± 2.90 years (range, 7–18) in patients with obesity and healthy controls, respectively ( p = 0.84). The mean area of the FAZ were 0.278 ± 0.10 mm 2 and 0.272 ± 0.11 mm 2 in children with obesity and in control participants, respectively ( p = 0.68). There were significant increases in the superior region of the parafoveal VD of SCP ( p = 0.008 for superior hemisphere and p = 0.003 for superior quadrant). There was no significant difference in any measure of the macular DCP and peripapillary region ( p > 0.05, for all). Conclusion: Increased vascular density measurements were found in the superior part of the parafoveal region of SCP in children with obesity. The results of the study should be taken into consideration during the course of the disease to define whole systemic response to obesity in childhood and will be of interest for pediatrician's clinical practice.